Causative factors and rehabilitation of patellar tendinopathy: A systematic review - Sanell Morgan; Elizabeth C. Janse van Vuuren; Frederik F. Coetzee (AOSIS, 2016)
Background: Patellar tendinopathy (PT) is a common chronic pathology of the knee, with a high prevalence in athletes and the general population. Objectives: The objectives of this article were to systematically investigate all the evidence applicable to the intrinsic and extrinsic causative factors and rehabilitation of PT, and then integrate and link rehabilitation with the main causative factors identified. Method: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Various tools were used to evaluate the methodological quality of the eligible articles. Data were interpreted descriptively, and the causative factors and rehabilitation of PT were analysed. Results: Twenty studies were included in the review. The distinctive factor responsible for PT is the mechanical theory. Seven intrinsic and four extrinsic risk factors were identified, with the main intrinsic risk factors being muscle flexibility and strength, and extrinsic risk factors being acquisition and level of skills. PT can be treated with numerous different therapeutic modalities, although eccentric muscle training showed exceptional results. The intrinsic and extrinsic risk factors can only be transformed and reduced by rehabilitation, which is inevitable to improve PT pain and function. Conclusion: The essence of an integrated management protocol for PT is to identify the dominant contributing factors, whether intrinsic or extrinsic, and to reduce the load on the patellar tendon by modifying these factors by either rehabilitation intervention or direct modification of the equipment or environment to obtain a positive outcome towards pain management and function.